(untitled) (Annals of Medical Research, 2021)
Aim: PFAPA syndrome which we thought was not well recognized. The high fever clinic of PFAPA syndrome usually mimics infectious conditions therefore it can lead to unnecessary and costly diagnostic tests and treatments. We evaluated the medical history, clinical findings and outcomes of pediatric patients diagnosed with PFAPA syndromeMaterial and Methods: In Mustafa Kemal University, Faculty of Medicine, Department of Pediatrics between September of 2016 and 2017, demographics, clinical, laboratory, diagnosis and treatment data of our patients diagnosed with PFAPA syndrome were retrospectively reviewed.Results: 68 patients were studied in our study, of which 27 (39.7%) were females and 41 (6.2%) were males. The mean age at onset of symptoms was 21.7 months. The mean age of diagnosis was 34.9 months. The mean duration between episodes of the disease was 27.05 days and the mean duration of episodes was 4.91 days.Conclusion: PFAPA syndrome which causes unnecessary costly examinations and treatments should be kept in mind in high fever clinic and also medical treatment was found to be effective in patients with PFAPA syndrome.Keywords: Child; Medical Treatment; PFAPA Syndrome; Periodic Fever.